2021
DOI: 10.3390/app11177818
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study Report on the Antioxidant and Phenolic Content of Selected Mediterranean Functional Foods, Their Consumption Association with the Body Mass Index, and Consumers Purchasing Behavior in a Sample of Healthy Greek Adults

Abstract: Functional food consumption is shown to have a positive effect on anthropometric parameters and human health promotion. In addition, consumers seem to be more interested in food choices, that may have a positive effect on their health. The current study aimed to identify the antioxidant and phenolic content of naturally functional foods from the Mediterranean diet and to investigate consumer behavior towards their consumption in terms of their weight control, as well as their purchasing behavior and knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Comparing the results of the antioxidant content between the PPE and BE, these results can agree with the results of Kalita et al who found higher antioxidant content also in PPE than BE using ORAC assay ( Kalita & Jayanty, 2014 ). Another study by Kandyliari et al can be correlated found higher antioxidant content in pomegranate than the blueberries ( Kandyliari et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…Comparing the results of the antioxidant content between the PPE and BE, these results can agree with the results of Kalita et al who found higher antioxidant content also in PPE than BE using ORAC assay ( Kalita & Jayanty, 2014 ). Another study by Kandyliari et al can be correlated found higher antioxidant content in pomegranate than the blueberries ( Kandyliari et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, plant byproducts and herbal extracts were utilized to prepare aqueous extracts that were easily incorporated into the final food products. However, an important factor that remains is the final organoleptic characteristics of fortified dairy products, as consumers usually choose taste over the health benefits of functional foods [12].…”
Section: Discussionmentioning
confidence: 99%
“…The term was first used in the 1980s by the Ministry of Health and Welfare of Japan and describes food products that maintain beneficial health effects for human functions while also remaining nutritious [10,11]. Bioactive compounds containing antioxidants, polyphenols, carotenoids, fibers, and phytosterols have been used as sources of functional ingredients [12]. Herbs have therefore been characterized as plant based functional foods, as they constitute a great source of antioxidants [13].…”
Section: Introductionmentioning
confidence: 99%
“…The 96-well microplate remained in the dark for 30 min and then the relative absorbance of the samples was measured at 595 nm in a spectrophotometer using Magellan™ data analysis software. The data were expressed as FeSO4 concentration (µM) [47,52,54].…”
Section: Determination Of Antioxidant Activity (Frap Assay)mentioning
confidence: 99%